Extremely rare cause of acute urinary retention: Guillain-Barré syndrome - Ag, Zehra Nur; Kirik, Serkan; Tartar, Tugay; Agar, Buket Esen; Tas, Nevsun Pihtili (Galenos Publ House, 2025)
Guillain-Barr & eacute; syndrome (GBS) is an acute immune-mediated demyelinating disease. Early recognition of this disease is crucial as it can progress to life-threatening conditions such as respiratory failure or autonomic dysfunction. Typical clinical signs of GBS include progressive weakness of the extremities, bulbar muscles, and ophthalmoplegia. In pediatric cases, acute bladder dysfunction is more suggestive of acute myelopathy. In this study, we aimed to raise awareness about this rare but serious condition by presenting one of the youngest pediatric GBS cases in the literature, who presented with acute urinary retention as the first finding and was successfully treated with intravenous immunoglobulin.
Keywords: acute urinary retention; Guillain-Barr & eacute; syndrome; pediatric